Why Are Mothers Working Longer Hours in Austria than in Germany? A Comparative Micro Simulation Analysis - Helene Dearing; Helmut Hofer; Christine Lietz; Rudolf Winter-Ebmer; Katharina Wrohlich (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Labor force participation rates of mothers in Austria and Germany are similar, however full-time employment rates are much higher among Austrian mothers. In order to find out to what extent these differences can be attributed to differences in the tax transfersystem, we perform a comparative micro simulation exercise. After estimating structural labor supply models of both countries, we interchange two important institutional characteristics of the two countries, namely (i) the definition of the tax unit within the personal income tax and (ii) the parental leave benefit scheme. As our analysis shows, differences in mothers? employment patterns can partly be explained by the different tax systems: While Germany has a system of joint taxation with income splitting for married couples, Austria taxes everyone individually, which leads to lower marginal tax rates for secondary earners than the German system.
Keywords: H24; H31; J22; 330; labor supply; micro simulation; family policy; income taxation; Austria; Germany; Arbeitszeit; Mütter; Frauen; Arbeitsangebot; Familienpolitik; Einkommensteuer; Schätzung; Deutschland; Österreich